The anti-hepatocellular carcinoma effects of polysaccharides from Ganoderma lucidum by regulating macrophage polarization via the MAPK/NF-κB signaling pathway. Issue 7 (8th March 2023) - Li, Guo-li; Tang, Jia-feng; Tan, Wen-li; Zhang, Tao; Zeng, Di; Zhao, Shuang; Ran, Jian-hua; Li, Jing; Wang, Ya-ping; Chen, Di-long
Abstract :   Ganoderma lucidum  polysaccharide (GLPS) can inhibit hepatocellular carcinoma (HCC). But the mechanism of GLPS's effect is little known. This data showed that GLPS can regulate MAPK/NF-κB signaling responsible for M1 polarization in anti-HCC. Abstract : The response of macrophages to environmental signals demonstrates its heterogeneity and plasticity. After different forms of polarized activation, macrophages reach the M1 or M2 activation state according to their respective environment. Ganoderma lucidum polysaccharide (GLPS) is a major bioactive component of Ganoderma lucidum, a well-known medicinal mushroom. Although the immunomodulatory and anti-tumor effects of GLPS have been proven, GLPS's effect on inhibiting hepatocellular carcinoma (HCC) by regulating macrophage polarization is little known. Our data showed that GLPS notably inhibited the growth of a Hepa1-6 allograft. The expression of M1 marker CD86 was higher in the tumor tissue of the GLPS treatment group than in the control group in vivo . In vitro, the phagocytic activity and NO production of macrophages were increased by GLPS treatment. Moreover, it was discovered that GLPS was able to increase the expression of the M1 phenotype marker CD86, iNOS, and pro-inflammatory cytokines comprising IL-12a, IL-23a, IL-27 and TNF-α, but inhibited macrophage polarization towards the M2 phenotype by decreasing the expression of CD206, Arg-1, and inflammation-related cytokines comprising IL-6 and IL-10. The data suggest that GLPS may regulate macrophage polarization. Mechanistically, GLPS increased the phosphorylation of MEK and ERK. In addition, the phosphorylation of IκBα and P65 was increased by GLPS treatment. These data showed that GLPS can regulate the MAPK/NF-κB signaling pathway responsible for M1 polarization. In a nutshell, our research puts forward a new application of GLPS in anti-HCC treatment by regulating macrophage polarization through activating MAPK/NF-κB signaling.